Empowerment Of Bamboo Weaving Crafts Business In The “Aishwarya Asih” Business Group In Sulahan Village, Bangli Regency - Maharani, Ida Ayu Dinda Priyanka; Soraya, Dewi; P. Putra, I Gst. B Ngr (MOVE: Journal of Community Service and Engagement, 2024)
Bangli Regency is rich in bamboo plants, namely plants belonging to the graminae family (grasses) and has a very flexible texture and is easy to create into various kinds of craft products. The business group that is a partner in the 2024 community service program is called the "Aishwarya Asih" Business Group, chaired by Ni Wayan Sukaini. The problems faced by partners are 1) product marketing which is still carried out conventionally, 2) other problems are in the process of recording product sales transactions, 3) problems in the production sector, namely related to the availability of facilities and infrastructure. The solutions provided are, 1) provision of a website and online marketing training and assistance, 2) training and assistance in recording digital financial transactions, 3) provision of supporting facilities and infrastructure for production.